Penyusunan Menu Gizi Seimbang di Posyandu Teratai - Zita Atzmardina; Clarissa Felicia; Decven Angela Sugiarto; Caroline Costrila; Barii Ikraam Majiid Ahmad (jurnal ABDIMAS Indonesia, 2025)
Stunting is a condition where a toddler has a length or height that is less than their age. This is a chronic nutritional problem experienced by toddlers, especially in the first 1000 HPK (First Days of Life). WHO (World Health Organization) data in 2020 shows that 22.2% or 149.2 million toddlers worldwide suffer from stunting. Based on data from the SKI (Indonesian Health Survey) in 2023, the prevalence of stunting in Indonesia is 21.6%. Based on data from the Health Center as of July 2024, there were 51 cases of stunting. In the same period in the previous year, there were 44 cases of stunting at the end of July 2023. The purpose of this activity is to increase knowledge about compiling a balanced nutritional menu at the Teratai Posyandu. Counseling as a method for explaining the preparation of a balanced nutritional menu. The results obtained were that all participants were able to work together in designing a balanced nutritional menu. It can be concluded that this activity was successful because participants were able to repeat the explanation given and this activity could be carried out periodically so that there was a decrease in stunting cases in the health center's work area.